Effects of Microbial-Mineral Interactions on Organic Carbon Stabilization in a Ponderosa Pine Root Zone: A Micro-Scale Approach - Dohnalkova, Alice C.; Tfaily, Malak M.; Chu, Rosalie K.; Smith, A. Peyton; Brislawn, Colin J.; Varga, Tamas; Crump, Alex R.; Kovarik, Libor; Thomashow, Linda S.; Harsh, James B.; Keller, C. Kent; Balogh-Brunstad, Zsuzsanna (Frontiers in Earth Science, 2022)
Soil microbial communities affect the formation of micro-scale mineral-associated organic matter (MAOM) where complex processes, including adhesion, aggregate formation, microbial mineral weathering and soil organic matter stabilization occur in a narrow zone of large biogeochemical gradients. Here we designed a field study to examine carbon stabilization mechanisms by using in-growth mesh bags containing biotite that were placed in a ponderosa pine root zone for 6 months and compared to the surrounding bulk soil. We sought to determine the composition of the microbial community in the mesh bags compared to the surrounding soils, analyze the direct interactions between microbes and biotite, and finally identify the nature of the newly formed MAOM within the mesh-bags. Our results revealed that minerals in the mesh bags were colonized by a microbial community that produced organic matter in situ. The 16S rRNA gene sequencing and ITS2 region characterization showed phylogenetic similarity between the mesh bag and bulk soil archaea/bacteria and fungi microbiomes, with significant differences in alpha- and beta-diversity and species abundances. Organic matter pools in the mesh bags, analyzed by Fourier transform ion cyclotron resonance mass spectrometry, contained protein- (peptides) and lipid-like compounds while the bulk soil OM was comprised of lignin-like and carboxyl-rich alicyclic molecules. These results support that the newly formed biotite associated organic compounds have a microbial signature in the mesh bags. High-resolution electron microscopy documented strongly adhered organic compounds to biotite surfaces, formation of microaggregates, elemental uptake at the microbe (organic matter)-mineral interface, and distortion of biotite layers. Overall, this study shows the direct and indirect involvement of soil microbial communities from the root zone of ponderosa pine in the formation of MAOM, soil organic carbon stabilization, microaggregation, and mineral weathering at micro- and nano-scales.